2021
DOI: 10.3390/ijms22136702
|View full text |Cite
|
Sign up to set email alerts
|

Renin-Angiotensin System in Pathogenesis of Atherosclerosis and Treatment of CVD

Abstract: Atherosclerosis has complex pathogenesis, which involves at least three serious aspects: inflammation, lipid metabolism alterations, and endothelial injury. There are no effective treatment options, as well as preventive measures for atherosclerosis. However, this disease has various severe complications, the most severe of which is cardiovascular disease (CVD). It is important to note, that CVD is among the leading causes of death worldwide. The renin–angiotensin–aldosterone system (RAAS) is an important part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 76 publications
(88 reference statements)
0
38
0
1
Order By: Relevance
“…The imbalance between renin and angiotensin II can lead to a large number of chronic and acute diseases [ 64 , 65 ], and plaque formation induced by angiotensin II in the early stage is one of the most important effects of RAAS on atherosclerosis [ 66 ], while under pathological conditions, RAAS also contributes directly or indirectly to the development of atherosclerosis and its various complications through its effects on other systems [ 67 ]. In addition to this, when renin and angiotensin II are imbalanced, the RAAS detrimental axis will also increase the release of inflammatory cytokines, and generate and increase oxidative stress; these pathological changes will further promote the formation of atherosclerosis, exacerbated IR, and decreased insulin secretion [ 66 , 68 ]. On the other hand, it should also be noted that serum hepcidin and hepcidin/ferritin ratio also play an important role in the development of IR and diabetes [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance between renin and angiotensin II can lead to a large number of chronic and acute diseases [ 64 , 65 ], and plaque formation induced by angiotensin II in the early stage is one of the most important effects of RAAS on atherosclerosis [ 66 ], while under pathological conditions, RAAS also contributes directly or indirectly to the development of atherosclerosis and its various complications through its effects on other systems [ 67 ]. In addition to this, when renin and angiotensin II are imbalanced, the RAAS detrimental axis will also increase the release of inflammatory cytokines, and generate and increase oxidative stress; these pathological changes will further promote the formation of atherosclerosis, exacerbated IR, and decreased insulin secretion [ 66 , 68 ]. On the other hand, it should also be noted that serum hepcidin and hepcidin/ferritin ratio also play an important role in the development of IR and diabetes [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of the balance between the two branches of RAS under different physiopathological conditions furnish novel therapeutic targets that may mitigate the development of CVDs [ 86 ]. Previous studies have confirmed the cardioprotective effects of ACE2 activators and ACE inhibitors (ACEIs) against MI-induced cardiac injure [ 87 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we must be aware that in addition to statins, all of our patients have been treated for more than six months also with ACE inhibitors/sartans, β blockers, and acetylsalicylic acid. The effect on the parameters of inflammation is well-recognized for statins [ 16 , 17 ], ACE inhibitors/sartans [ 29 ], β blockers [ 30 ], and acetylsalicylic acid [ 31 ], while all of them except β blockers also affect coagulation and fibrinolysis [ 16 , 17 , 29 , 31 ]. The inflammatory cytokine IL-1β stimulates the endothelial cells and leukocytes to produce intracellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%